A prominent footballer as a role model for young athletes - Paweł Kalinowski; Oskar Kluj; Damian Jerszyński (Nicolaus Copernicus University in Toruń, 2020)
The aim of this study is to illustrate the need for personal role models for young athletes on the example of the Portuguese player Cristiano Ronaldo. Currently, the requirements of young football adepts are constantly growing. Football is booming and evolving very quickly. The players exceed the limits of their own field and intellectual abilities. Along with this, the awareness of players increases. And hence the need for individual development increases as well. Coping with the difficulties that arise on the path of a young athlete becomes the norm. Sports authorities play an important role in the training process. Nowadays, young people look for authorities among the most prominent athletes. One example of such prominent athletes is the Portuguese footbal player Cristiano Ronaldo, who is characterized by an exceptional attitude to training and an exemplary pursuit of his own sports career. The example of a great footballer shows the way full of sacrifices, which is necessary to achieve high sports results in the international arena. The work will present an attempt to refer to role models in sport on the example of the excellent player and illustrating young players who pursue a specific goal that achieving specific results often involves overcoming many obstacles.